PENGARUH LATIHAN VARIASI TEKNIK PASSING TERHADAP KETERAMPILAN PASSING DAN STOPING PADA TIM SEPAKBOLA WIJAYA KESUMA DESA SIKEBAU JAYA KECAMATAN ROKAN IV KOTO - Ansori, Muhammad Isa; Slamet, Slamet; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this study is les hes passing and stoping in the game of football on the soccer team Wijaya Kesuma Village Sikebau Jaya District Rokan IV Koto. The research aims to find out if there is the influences of exercise variety of techniques of passing on skills of passing and stoping, so, when snap of the ball (passing) get the capabilities of passing on a good. The research is experimental, the data in this research is the whole population of 16 people. The instruments used in this research is a test of footbal and hold the ball (passing and stoping), it aims to measure the abilityto kick and hold the ball. After that, the data is processed with statistics,to test normality with a lilifors test at significance level α (0.05). The hypothesis put forward is the influence of the exercise variety of techniques of passing on skills of passing and stoping. Based on the analysis of statistical data, there is an average Pree-test of 13,87 and the average post-test by 15,75, then the data is normal with an increase of 1,88. Based on t test analysis produces Ttabel >Thitung of 8,75 and 1,753, meaning Thitung> Ttabel. Thus, there is the influence of exercise of variety of techniques of passing on skills of passing and stoping on the soccer team Wijaya Kesuma Village Sikebau Jaya District Rokan IV Koto.Keywords : variety of techniques of passing, The skills of passing and stoping